Rol de las empresas en la sociedad contemporánea. - Rodríguez Calderón, Greivin (2014)
The company´s traditional role used to be limited to generate profits to its owners;however, as a result of an always changing market, boosted, mostly by both a more demanding and interested customer in the profound impact that production activities have on the society and environment pollution.Te company´s functional paradigm has changed, establishing it as a entity of development, that is the reason why concepts such as Corporate Social Responsibility (CSR) has been created, which is more than simple philanthropy and requires a commitment to Social Responsibility.This article provides a global vision about a company´s evolution in society and how some intangible factors related to the brand and reputation;more than the product it self have a direct influence when consumer decides to buy something.